2002
DOI: 10.1093/jn/132.9.2574
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperglycemia and Insulin Sensitivity Differ among Lean Young Adults of Different Ethnicities

Abstract: Both postprandial hyperglycemia and insulin resistance (IR) have implications for the development of cardiovascular disease. The present study was designed to examine differences in postprandial glycemia and insulin sensitivity among young adults of different ethnic origins. Lean, healthy subjects (n = 60) from five ethnic groups [20 European Caucasians, 10 Chinese, 10 South East (SE) Asians, 10 Asian Indians and 10 Arabic Caucasians] were matched for age, body mass index, waist circumference, birth weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 17 publications
7
146
2
3
Order By: Relevance
“…Older age, non-Caucasian ethnicity and high triglycerides are associated with insulin resistance (Chen et al, 1985;Haffner et al, 1996;Harris et al, 1998;Dickinson et al, 2002;Lewis et al, 2002;Lam et al, 2007), which increases postprandial glucose by increasing the hepatic glucose output and reducing the muscle glucose uptake (Hwang et al, 1995;Bruttomesso et al, 1999). However, fasting insulin, a measure of insulin sensitivity (Laakso, 1993;Clausen et al, 1996), was not independently related to AUC for any food.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, non-Caucasian ethnicity and high triglycerides are associated with insulin resistance (Chen et al, 1985;Haffner et al, 1996;Harris et al, 1998;Dickinson et al, 2002;Lewis et al, 2002;Lam et al, 2007), which increases postprandial glucose by increasing the hepatic glucose output and reducing the muscle glucose uptake (Hwang et al, 1995;Bruttomesso et al, 1999). However, fasting insulin, a measure of insulin sensitivity (Laakso, 1993;Clausen et al, 1996), was not independently related to AUC for any food.…”
Section: Discussionmentioning
confidence: 99%
“…Three earlier studies showed higher fasting insulin concentrations and HOMA-IR values in South Asians or Asian Indians as compared to other ethnic groups, [14][15][16] but did not assess their relationships with peripheral and truncal subcutaneous fat, abdominal adiposity, and body fat, and included either a small number of prepubertal children or young adults. Whincup et al 14 studied surrogate markers of insulin resistance in an unspecified number of Asian Indian children among 40 South Asian prepubertal children (9-11 y age) in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] These studies have dealt with limited numbers of offspring of migrant Asians who are generally more affluent, and have an acculturated diet and lifestyle as compared to those living in India. A population-based study of insulin resistance, anthropometric, and cardiovascular risk factor profile in postpubertal Asian Indian children has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The net effect is a reduction in functional beta cell mass in the type 2 diabetic state. Information drawn from previously published work [119,120] Carbohydrates, serum lipids and hepatic lipogenesis…”
Section: Carbohydrates and Glucose Homeostasismentioning
confidence: 99%